2014
DOI: 10.1242/dev.112607
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2-mediated repression of a transcriptional pathway upstream of Mmp9 maintains integrity of the developing vasculature

Abstract: Maintenance of vascular integrity is required for embryogenesis and organ homeostasis. However, the gene expression programs that stabilize blood vessels are poorly understood. Here, we show that the histone methyltransferase Ezh2 maintains integrity of the developing vasculature by repressing a transcriptional program that activates expression of Mmp9. Inactivation of Ezh2 in developing mouse endothelium caused embryonic lethality with compromised vascular integrity and increased extracellular matrix degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 48 publications
6
40
2
Order By: Relevance
“…Transplantation experiments revealed that the effects of Kdm2b in HSPC maintenance and lymphopoiesis are cell intrinsic (Figure 4). Strikingly, a similar phenotype has been reported for Tie2-Cre Ezh2 fl/fl embryos, which also lacked definitive hematopoiesis and failed to develop beyond E13.5-E14.5, and in adult mice, Ezh2 was indispensable for lymphopoiesis (51)(52)(53). Similarly, deletion of Suz12 led to a rapid exhaustion of HSPCs and also impaired lymphopoiesis (54).…”
Section: Discussionsupporting
confidence: 71%
“…Transplantation experiments revealed that the effects of Kdm2b in HSPC maintenance and lymphopoiesis are cell intrinsic (Figure 4). Strikingly, a similar phenotype has been reported for Tie2-Cre Ezh2 fl/fl embryos, which also lacked definitive hematopoiesis and failed to develop beyond E13.5-E14.5, and in adult mice, Ezh2 was indispensable for lymphopoiesis (51)(52)(53). Similarly, deletion of Suz12 led to a rapid exhaustion of HSPCs and also impaired lymphopoiesis (54).…”
Section: Discussionsupporting
confidence: 71%
“…Sections were stained as previously described (Delgado-Olguin et al, 2014). Primary antibodies and dilutions were: G9a (Cell Signaling ;Tie2-Cre;Rosa mT/mG placentae at E13.5.…”
Section: Immunofluorescencementioning
confidence: 99%
“…These dramatic gene expression changes imply a role for global transcriptional regulators during the transition. Epigenetic regulators coordinate global gene expression patterns by modifying chromatin structure and controlling the access of transcription factors to their target genes, and also control vascular development (Delgado-Olguin et al, 2014;Griffin et al, 2011). The euchromatic histone-lysine N-methyltransferase (G9a; also known as Ehmt2) can both repress and activate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, we discovered that d-flow upregulated PKCf binding to the E3 SUMO ligase PIAS4 and stimulated p53 SUMOylation and, subsequently, EC apoptosis (51). Taken Epigenetic events include DNA methylation (15,23,28,76,82,113,115), histone modification (6,8,129), and the actions of small and noncoding RNAs (53,91,97). DNA methylation subjects the 5-position of cysteine (the fifth base of DNA) to dynamic postsynthetic covalent modification (43).…”
Section: Erk5 Sumoylationmentioning
confidence: 90%
“…Epigenetic events include DNA methylation (15,23,28,76,82,113,115) and histone modification (6,8,129). The use of epigenetic chromatin markers to identify shear stress response elements (SSREs) in the promoters of flow-responsive genes, as well as the idea that protein post-translational modifications (PTMs) play a critical role in the modulation of epigenetic states, has been suggested (28,63,143).…”
mentioning
confidence: 99%